Single-phase white-emitting phosphors Ba3Ce(1−x−y)(PO4)3:xTb3+, yMn2+ and Ba3Ce(1−x−z)(PO4)3:xTb3+, zSm3+: structure, luminescence, energy transfer and thermal stability. Issue 32 (31st March 2017) - Xu, Shuchao; Wang, Zhijun; Li, Panlai; Li, Ting; Bai, Qiongyu; Sun, Jiang; Yang, Zhiping
Abstract : A series of Ba3 Ce(1−x−y) (PO4 )3 : x Tb 3+, y Mn 2+ and Ba3 Ce(1−x−z) (PO4 )3 : x Tb 3+, z Sm 3+ phosphors were synthesized by a high temperature solid-state reaction. Abstract : A series of Ba3 Ce(1−x−y) (PO4 )3 : x Tb 3+, y Mn 2+ and Ba3 Ce(1−x−z) (PO4 )3 : x Tb 3+, z Sm 3+ phosphors were synthesized by a high temperature solid-state reaction. X-ray diffraction, luminescence and decay curves were used to characterize the phosphors. All the synthesized phosphors crystallized in the cubic unit cell with I 4̄3 d space group. Energy can be transferred from Ce 3+ to Tb 3+ /Mn 2+ /Sm 3+ in Ba3 Ce(1− x ) (PO4 )3 : x Tb 3+, Ba3 Ce(1− y ) (PO4 )3 : y Mn 2+, and Ba3 Ce(1− z ) (PO4 )3 : z Sm 3+ phosphors. Furthermore, the color of these phosphors can turn from cyan to green, blue to red, and cyan to pale pink. When Ba3 Ce(PO4 )3 was co-doped with Tb 3+ and Mn 2+ /Sm 3+, Tb 3+ could also transfer part of its energy to Mn 2+ /Sm 3+, and more importantly, a white emission can be achieved based on this energy transfer. The phosphors exhibited a good thermal stability, with correlated color temperatures of up to 3301 K, and a quantum efficiency as high as 51.2%. These results revealed that we managed to obtain good white emitting phosphors by co-doping Ba3 Ce(PO4 )3 with Tb 3+ and Mn 2+ /Sm 3+ .